Lip Prints: A Statistical Study of Morphological Patterns to Determine Sex Differences among Brahmins and Yadavs of the Bundelkhand Region of Uttar Pradesh, India - Saba Rashid; Anu Singla (Arab Journal of Forensic Sciences & Forensic Medicine, 2019)
Like fingerprints, lip prints are considered distinctive to an individual. A lip print found at the crime scene can help reveal the identity of the persons involved. The present study focuses on the differentiation of lip prints according to sex and studies the distribution of lip print patterns in various communities of the Bundelkhand region of Uttar Pradesh, India. A total of 400 samples of lip prints were collected from males and females of age group 18-24 years, belonging to Brahmins and Yadavs from the Bundelkhand region of Uttar Pradesh. The most prevalent was Type I lip print in Brahmin males and Type II in Brahmin females, whereas Type III pattern was the most common in Yadav males and females. When Lip patterns were statistically evaluated based on the sex differences in Brahmins, Type II and I patterns may help in sex determination. Whereas, when the data is compared between males and females of Yadavs, Type III lip print had high predominance in comparison to other patterns but may not help in sex determination.